A study on the relationship between job satisfaction and affective commitment among support staff in selected public sector departments in Bangunan Wisma Persekutuan Temerloh, Pahang / Mohamad Shahrul Nizam Mohd Alwi - Mohd Alwi, Mohamad Shahrul Nizam (2016)
The purpose of this research was to investigate the relationship between job satisfaction and affective commitment among support staff in selected public sector departments in Bangunan Wisma Persekutuan Temerloh, Pahang. This correlational research used a stratified random sampling techniques and the sample size was determined using Krejcie and Morgan (1970). Survey questionnaires were distributed to 56 support staff in selected public sector organisation, which was adopted from Web Survey Master (2016), Spector, Jaros (2007), and Maslic Sersic (1999). The questionnaires were analysed using SPSS V-21 to indentify the result. Most of the respondents were female workers, age between 31 to 40 years old, from group C support staff, and have 5 to 10 years working experience. The finding showed that there was a strong positive relationship between job satisfaction and affective commitment (r=0.70, p=0.00). Moreover, the correlation were positive significant relationship as a result for benefit (r=0.68, p=0.00), salary (r=0.66, p=0.00), and promotion (r=054, p=0.00). The value of R-square showed that 52% of the variances in job satisfaction can be predicted from the variable of salary, fringe benefit and promotion. The regression model consisting of salary, fringe benefit, and promotion toward affective commitment was significant at 0.05 level F(3, 52)=18.581, <0.05. The finding however, showed there was no relationship between length of support staff service and their affective commitment. It is recommended that organization provides trainings, encourage teamwork, conduct counseling program and meeting, as well as implement promotion to increase affective commitment among support staff. Future study, should focus on private sector, as well as others elements of job satisfaction such as supervision, job security and others in order to gain more information.